Proposal of a methodology for achieving a LEED O+M certification in historic buildings. (December 2017) - Mazzola, E.; Mora, T. Dalla; Peron, F.; Romagnoni, P.
Abstract: Nowadays resources are running out quickly, it's necessary to consider how the construction industry influences the environment using different materials and sources during all the building's life cycle. For this reason, in every transformation phases it's necessary to consider concepts as sustainability and green buildings. These are diffused from hundreds kind of green assessment tools, developed to measure sustainability goals in building sector and to compare the project with possible best practices or other green buildings. In this background, the rating system LEED (Leadership in Energy and Environmental Design) aims to examine and classify buildings according to energetic and environmental requirements. The particular LEED O+M (Building Operations and Maintenance) is developed for existing buildings undergoing improvement work or little to no construction and is based on the operative and management aspects. The certification process results, at a first analysis, hard to follow due to the complexity of internal parameters and the documentation required. The paper consists in a methodology and in an univocal work program of LEED O+M, trying to obtain the minimum requested certification score with optimization of the technical resources and documents. This methodology has application in a case study of historic building: the Ca' Rezzonico Museum, in the center of Venice.